Dorsolateral Onlay OMG Urethroplasty through Unilateral Urethral Mobilization in Anterior Urethral Stricture - Our Experience in Dhaka Medical College Hospital and Salam Urology & Transplantation Foundation of Bangladesh (SUTF) - Islam, MF; Haque, ME; Islam, MW; Hooda, MN; Alam, MS; Naser, MF; Awal, MA; Rasul, A; Alam, MS; Rahman, MA; Kaisar, I; Chow, MR; et al. (Bangladesh Journal of Urology, 2012)
Introduction: Circumferential urethral mobilization may result in ischemia of urethra in conventional anterior dorsal onlay urethroplasty. We performed dorsolateral onlay OMG urethroplasty in anterior urethral stricture through unilateral mobilization of urethra to preserve its vascular supply. Objective: To evaluate the feasibility and short term outcome of using dorsolateral onlay OMG urethroplasty in anterior urethral stricture through unilateral urethral mobilization. Method: In this prospective study, 27 patients with average age of 38 years underwent anterior dorsolateral onlay OMG urethroplasty through unilateral urethral mobilization in tertiary care hospital. In all patients, the surgical approach to the anterior urethra was made only along one side leaving the urethra attached to the corpora cavernosa on the opposite side thus preserving its vascular supply intact on one side. The cause of stricture was instrumentation in four cases (14%), lichen sclerosis in thirteen cases (48%), unknown in seven cases (25%) and infection in three cases (11%).The stricture site was bulbar in 10 cases and panurethral in 17 cases. Average length of the stricture segment was 4cm and 9 cm in bulbar and panurethral respectively. Of 27 patients, 20 received previous treatment. Clinical outcome was considered a failure when postoperative Qmax was <10ml/sec and/ any instrumentation were needed. Patient who underwent previous urethral reconstruction surgery was excluded from the study. Result: Of the 27 patients, 25 had (92%) successful outcome and 2 (8%) were failure. Two failed cases underwent successful optical internal urethrotomy. Follow up period was 4 months to 20 months. Conclusion: Dorsolateral onlay urethroplasty of anterior urethral stricture preserving vascular supply along one side of its entire length of reconstruction is a simple and may be a reliable solution for better outcome. Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.22-25